Differential gene expression mediates physiological responses to perceived predation risk in a developmentally plastic vertebrate, the northern leopard frog (Lithobates pipiens) - Cambridge, Tucker W.; Donaldson, Michael E.; Kerr, Leslie R.; Lesbarrères, David; Longhi, Jessica N.; Row, Jeffrey R.; Saville, Barry J.; Murray, Dennis L. (Frontiers in Ecology and Evolution, 2025)
Prey can respond to predation risk through developmental plasticity, generating anti-predator phenotypes. These inducible defenses arise from changes to the stress axis, and neuroendocrine-triggered gene regulation is a likely mechanism influencing such phenotypes. As tadpoles, amphibians improve their escape performance by modifying tail shape in response to perceived predation risk (PPR), and this process should involve tissue and developmentally specific gene regulation. We exposed Lithobates pipiens tadpoles to PPR from Aeshnidae predators and measured tail morphology and transcriptomic response across different tissues (head and tail) and development (pre-metamorphosis to pro-metamorphosis). We found that PPR induced plasticity in tail shape, and this response was suppressed when tadpoles were also exposed to a glucocorticoid synthesis inhibitor. Differential gene expression was associated with predation stress across head and tail tissue, and developmental stage. Predator-exposed tadpoles exhibited up-regulation of genes responsible for muscle tissue and nervous system development, primarily in tail tissue and in pre-metamorphosis. PPR broadly influenced pathways across tissues and metamorphosis, including developmental, endocrine, and immune system pathways. This study provides an important step in understanding transcriptomic responses during predator induced morphological change, and demonstrates that gene expression, as induced by perceived predation risk, is a prominent mechanism of developmental plasticity.